Rapid fabrication of near superhydrophobic aluminium surface through nanosecond laser texture and heat treatment. Issue 1 (1st January 2022) - Fan, Changfeng; Wang, Xue; Liu, Yancong; Li, Chengkai; Liu, Xiao
Abstract: Controlling surface wettability inspired by nano structure of lotus leaf has attracted much attention. The superhydrophobicity on the metals is significant for the applications including water repellence, self-cleaning, anti-corrosion, and reduction of drag. Herein a near superhydrophobic surface of 5051 aluminium has been fabricated by employing a combination of nanosecond laser texture and heat treatment, without using any toxic chemicals. The aluminium surface was textured by fibre nanosecond laser and then heat treated at 150 °C to create the near superhydrophobic surface. The evolution of heat treatment time with respect to contact angle measurements has been investigated. The contact angle became 0° when processed by two different kinds of laser textures (sinusoid pattern and grid pattern). The influence of heat treatment on the wettability of the laser textured aluminium surface was studied. The contact angle exhibits 134.88° and 136.97° for sinusoidal pattern and grid pattern with 72 hours heat treatment, respectively. The mechanism for fast wettability conversion time is discussed. This method is a rapid and environment-friendly process, which is feasible for fabrication.